Circadian rhythm of blood pressure in patients dependent on ventricular demand pacemakers. - Davies, A B (1984)
The reported circadian rhythm of blood pressure variability with a rise in pressure before awakening has been the subject of controversy. Previous studies have suggested that since heart rate continues to fall before awakening while blood pressure is rising these physiological variables are subject to different control mechanisms. To evaluate further the dissociation of heart rate and blood pressure changes in a group of patients with a fixed heart rate, 11 patients who were dependent on ventricular demand pacemakers underwent intra-arterial ambulatory blood pressure monitoring. Nine aged matched control subjects followed the same protocol. Circadian curves plotted from pooled hourly mean data showed that despite a fixed heart rate the circadian pattern persisted, although attenuated, with blood pressure rising several hours before its rapid rise on awakening. Physiological testing showed that despite a fixed heart rate systolic blood pressure rose in response to bicycle exercise, there was a postural fall in the blood pressure on tilting and a modified Valsalva response. There was considerable beat to beat variability resulting presumably from asychronous pacing. Hour to hour changes did not contribute to the differences between the two groups and were not responsible for attenuation of the circadian rhythm. It is concluded that blood pressure and heart rate control mechanisms may be dissociated, particularly in the period before awakening.